A short synthesis of 4-Hydroxypyrrolidine-2-One from Tetramic Acid Intermediates / Sharifah Nurin Zafirah, Noor Hidayah Pungot and Zurina Shaameri - Zafirah, Sharifah Nurin; Pungot, Noor Hidayah; Shaameri, Zurina (UiTM Cawangan Negeri Sembilan, 2022)
4-Hydroxypyrrolidine-2-one 1 is useful as intermediates for synthesising antibiotic and antidepressant agents. Nevertheless, most organic synthesis routes are long and require a long time to generate the desired compounds, consisting of two reactions steps. The first step involves synthesising pyrrolidine- 2,4-diones from N-Boc-amino acids via Meldrum's acid-mediated reaction and tetramic acid cyclisation. Generally, 1-(3-diemthylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC.HCl) is employed as a carboxyl activating agent in the reaction due to easy access and cost. In the present study, the short synthesis of 4-hydroxy pyrrolidin-2-one utilising N-Boc-alanine 2 and N-Boc-valine 3 as the amino acid was determined to produce tetramic acids 4 and 5. The present study employed easily obtainable starting chemical compounds and was less costly to synthesise the 5-substituted pyrrolidine- 2,4-diones via Meldrum's acid-mediated reaction and tetramic acid cyclisation. The amino acids employed were also readily protected by the tert-butoxycarbonyl (Boc) group to prevent the acids from reacting with other compounds. Resultantly, compounds 4 and 5 were successfully synthesised with 22% and 10% yields, respectively. The tetramic acids were then subjected to regioselective reduction with sodium borohydride (NaBH4) as the reducing agent in methanol to acquire compounds 6 (9%) and 7 (6%). All synthesised compounds were purified by column chromatography and characterised using nuclear magnetic resonance (1H and 13C NMR) spectroscopy.